RI 7856 Steam-Cured Bricks From Industrial Mineral Wastes - P. G. Pigott (The National Institute for Occupational Safety and Health (NIOSH), 1974)
This investigation by the Bureau of Mines demonstrated that building bricks can be produced by the steam-curing process from various types of industrial mineral wastes. Wastes, utilized to produce bricks, consisted of copper mill tailings, roofing granule fines, asbestos fines, and zinc mill tailings. Bonding of the wastes with either Ca(OH)2 or portland cement resulted in building bricks that met ASTM specification C73-67 for grade SW and MW bricks when evaluated in accordance with ASTM designation C67-66 on sampling and testing of brick. An economic evaluation of the process indicates the total operating cost per 1,000 bricks is about $36.